If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5-9x=3-(2-3x)-8
We move all terms to the left:
-5-9x-(3-(2-3x)-8)=0
We add all the numbers together, and all the variables
-9x-(3-(-3x+2)-8)-5=0
We calculate terms in parentheses: -(3-(-3x+2)-8), so:We get rid of parentheses
3-(-3x+2)-8
determiningTheFunctionDomain -(-3x+2)+3-8
We add all the numbers together, and all the variables
-(-3x+2)-5
We get rid of parentheses
3x-2-5
We add all the numbers together, and all the variables
3x-7
Back to the equation:
-(3x-7)
-9x-3x+7-5=0
We add all the numbers together, and all the variables
-12x+2=0
We move all terms containing x to the left, all other terms to the right
-12x=-2
x=-2/-12
x=1/6
| 2y+0.9=-1.04 | | 8(2x-5)-4x=-10+7x | | 4(b-65)=76 | | -342=-9x | | -x+3=4x-17/ | | 4x-8=10x-2 | | −4x+3=23. | | 1=3n | | 2(m-4)=8+2m | | a-1.7=-4.9 | | 23x-3=17 | | 2p-10=32 | | 4(4x-7)-5=16x-33 | | X^2+6x-7=x+3+5 | | 4=g/10 | | 2/3t-5=2 | | 33-(2c+3=2(c+5)+c | | t+22=6 | | -3z+-7=2 | | b/3-8=-4.5 | | -b+2(-3b+8)=23-6b | | r+-6=1 | | 5=1/4x+2 | | -9h=-10h+18 | | -1=x/4+7 | | 2y=-61+5(5y+3) | | -4m+7=m-18 | | 5(5t+1)=25t-7+12 | | 4=3n | | 9x-4(5-x)=6 | | 8=-7x-6+9x | | 4x-8=10–2 |